Pengaruh Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT.Hadji Kalla Toyota Kota Makassar - Sari, Emira; Riyanti, Rosita; Haslinda, Haslinda; Teriade, Teriade; Marsal, Marsal (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aimed to test whether Organization Culture and Work Environment to Employee Performance.Indepent variabel in this study is the Organization Culture and Work Environment.The dependent variabel is Employee Performance. This reseach was conduce on employees of The PT.Hadji kalla Toyota consisting of 35 respondents.This type research is quantitative research. Method data collection using the questionnaire. Data analysis using multiple linear regress ion. The resultd showed that Organizational Cultere and Work Enviroment is positive and significant effect towards employees performance.